Speech Acts in Multilingual Digital Classrooms: Miscommunication and Repair Strategies - Lilis Napitupulu; Evi Novalin Bako (English Language Teaching Prima Journal (ELT), 2026)
This article examines how speech acts are interpreted, misunderstood, and repaired in multilingual digital classrooms. Using a qualitative thematic literature review, it synthesizes studies on speech act theory, classroom discourse, translanguaging, digital communication, and repair organization. The review shows four recurring patterns: indirect directives are often misread, multilingual language choice may create trouble but also supports repair, platform features reshape pragmatic cues, and repair strategies help sustain participation. The article argues that miscommunication in digital classrooms should not be reduced to linguistic deficiency. It is an interactional event shaped by language ideology, power relations, digital affordances, and learners' multilingual repertoires. The study offers a sociopragmatic framework for analyzing classroom interaction and suggests practical ways to make multilingual digital teaching clearer, more inclusive, and more responsive to learners' communicative needs.